2016
DOI: 10.4103/2230-8210.176362
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in 7 years trends in cholesterol lipoproteins and lipids in India: Insights from a hospital database

Abstract: Objective:To determine gender differences and secular trends in total, low-density lipoprotein (LDL) and high DL (HDL) cholesterol and triglycerides using a large hospital database in India.Methods:All blood lipid tests evaluated from July 2007 to December 2014 were analyzed. Details of gender and age were available. Statin therapy was obtained at two separate periods. Trends were calculated using linear regression and Mantel-Haenszel X2.Results:Data of 67395 subjects (men 49,904, women 17,491) aged 51 ± 12 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 32 publications
5
16
1
Order By: Relevance
“…The described differences are usually small. Gupta et al [44] presented very similar correlations, simultaneously stressing that higher mean TC values in females appear after the age of 45 years. Since in our study the average age of females is statistically significantly higher than in males (e.g., in 2018, 55.71 versus 53.05 at p < 0.001), we consider these values as consistent with data from the available literature [1,45].…”
Section: Discussionmentioning
confidence: 83%
“…The described differences are usually small. Gupta et al [44] presented very similar correlations, simultaneously stressing that higher mean TC values in females appear after the age of 45 years. Since in our study the average age of females is statistically significantly higher than in males (e.g., in 2018, 55.71 versus 53.05 at p < 0.001), we consider these values as consistent with data from the available literature [1,45].…”
Section: Discussionmentioning
confidence: 83%
“…In a study utilizing hospital administrative database of more than 67,000 participants we reported prevalence of various dyslipidemias using a fasting sample. 38 In this cohort of mostly middle class men and women there was a high prevalence of various dyslipidemias ( Fig. 4 ).…”
Section: Indian Epidemiological Studiesmentioning
confidence: 77%
“…Participants (n = 5350, men 2935, women 2415) were evaluated for demographic, biophysical, and fasting biochemical risk factors. In the hospital-based study, all consecutive fasting blood lipid tests performed over a seven-year period were analyzed (n = 67347, men 49866, women 17481) 38 . The age-adjusted prevalence of severe hypercholesterolemia in population vs hospital based studies was total cholesterol 240–269 mg/dl in 5.0% vs 5.5%, 270–309 mg/dl in 2.3% vs 1.8% and ≥310 mg/dl in 0.3% vs 0.0.5%.…”
Section: Severe Hypercholesterolemiamentioning
confidence: 99%
“…More importantly, it highlights, which components of the MetS are more closely correlated with diabetes in this population. Previous studies in India have found that women have lower HDL than men and that cardiovascular risk factors (RFs) such as diabetes, hypertension, and smoking are highly prevalent[ 6 , 7 ]. Herein we report that a greater percent of AI males have increased fasting glucose, blood pressure, and triglycerides compared to females and that a greater percent of AI females have increased waist circumference and decreased HDL compared to males.…”
Section: Introductionmentioning
confidence: 99%